Meta-Analysis: The Impact of Heart Failure Medications in Improving Left Ventricular Function in Chemotherapy Induced Cardiomyopathy - Asharaf, Azzah Muhammad; Ansari, Mariyam; Ali, Lamis Elfateh Mohamed; Mahmoud, Yasmeen sharif; Ahmed, Ahmed Ibrahim haji; Mazhar, Muneeb; Khalid, Saif; alefari, Hamda hamad; Moussa, Sara El; M.Ali, Ahmad Wajdi (Cardiology and Cardiovascular Medicine, 2025)
Background: One major side effect of cancer treatment is chemotherapy induced cardiomyopathy (CIC), especially from anthracyclines and HER2-targeted drugs. Early administration of heart failure drugs such as beta-blockers (BBs), angiotensin receptor blockers (ARBs), statins, mineralocorticoid receptor antagonists (MRAs), ACE inhibitors (ACEIs) and more recent drugs like angiotensin receptor–neprilysin inhibitors (ARNIs) has demonstrated promising effects in reducing cardiac damage. Major cardiology societies like the American Heart Association (AHA), European Society of Cardiology (ESC), and American College of Cardiology (ACC) recommend these agents as the cornerstone of Guideline- Directed Medical Therapy (GDMT), which is the standard approach for treating heart failure and is being used to stop or reverse cardiac dysfunction in patients who have cardiomyopathy caused by cancer treatment. Objective: The objective of this study is to assess and compile the available data regarding the effectiveness of heart failure drugs in maintaining or improving left ventricular ejection fraction (LVEF) in patients suffering from cardiomyopathy caused by chemotherapy. Methods: This study includes peer reviewed studies which mainly are expert reviews, cohort studies, meta-analysis and randomized controlled trials (RCTs). Reports which focused on evaluating the impact of heart failure drugs on LVEF in populations exposed to chemotherapy were included. Pooled effect sizes, if available, were used to synthesize the data, and the I2 statistic was used to assess heterogeneity. Risk ratios and standardized mean differences were extracted to measure treatment effects across drug classes. Results: Among the best agents for improving left ventricular ejection fraction (LVEF) were enalapril (+7.6%, CI: 5.3–9.9%) and spironolactone (MD: +12.8%, CI: 7.9–17.7%) [1], [2]. In refractory cases, sacubitril/valsartan showed a high LVEF recovery [3]. Although ARBs showed mixed results, telmisartan stood out very effective because of its anti-inflammatory qualities [4]. The likelihood of LVEF recovery was considerably enhanced by early initiation of guideline directed medical therapy (GDMT) (OR = 9.39, p < 0.001) [5]. Heterogeneity was moderate to high (I² > 60%) and publication bias was minimal. Conclusion: In patients with chemotherapy induced cardiomyopathy, heart failure medications, especially when started early, significantly improve or preserve LVEF. Preventive and therapeutic cardio-oncology protocols should give priority to GDMT, particularly ACEIs, MRAs, and ARNIs.